PEMBUATAN SISTEM INFORMASI GEOGRAFIS PENENTU LOKASI POS POLISI LALU LINTAS WILAYAH PROBOLINGGO KOTA - Adhadina, Reesky Riko (University of Surabaya, 2016)
People who use motor vehicle progressively increasing and make traffic jams on the highway becomes very dense.With the Highway Environment which is getting dense, it takes traffic police posts that useful for organizing jammed prone areas. Every highway has different level of traffic fluency and safety within a certain time, so that traffic police posts which placed is just temporary. The Placement of Temporary Traffic Police Post are based by factors that allows traffic jams happen. The Probolinggo City Police Department are still comparing traffic jam factors of the highways to deciding the best area to place police post. When there are 2 (two) highways have the same or similar amount of factor values, will be hard to decide where is the right highway to be placed atemporary police post. Moreover, traffic police post marking point still using tacked pin on the map that is still attached to the meeting room walls, so that it will reducing efficiency of the traffic police member who wants to review the posts. The determination of the closest path for the member of traffic police still manually measure and looking at the conventional maps. It is difficult for the police to time-saving, for determine the route path. From the problems already mentioned above, it can be concluded that Probolinggo City Traffic Police Department need a system that can accommodate all of the activity for determining the best recommendation of temporary traffic police posts and process to be an information. Therefore, will be created a geographic information systems to determine the location of the temporary traffic police post probolinggo city. This system is designed to help the activities in the traffic units at Probolinggo City and process to be an information. This system determining the traffic post using Analytical Hierarchy Process (AHP) method. This method uses a traffic jam factors as parameter for determining traffic police posts, so that the traffic polices get the best recommendation for placing the temporary traffic police post. The Evaluation to the system is done by 2 (two) stages, that are verification and validation. The Result from the tests and evaluation, can be concluded that this system helps Probolinggo City Traffic Police Department for determining temporary traffic police posts, moreover they get an accurate information for organizing temporary traffic police post.